An Evaluation of the Nutritional Content of Rattan Shoots as a Potential Learning Resource for Local Wisdom-Based Education - Musdalifah Nurdin; Syech Zainal; Nasria Nasria; Raya Agni; Samsurizal M Suleman; Siti Eneng Sururiyatul Mu’aziyah; Moh Sabran (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: Rattan, a valuable resource for both industry and local food, is evaluated for its nutritional content in this study. The research explores its potential as a learning resource based on local wisdom in Sibado Village, Sirenja District, aiming to raise awareness and promote sustainable use within the community. Methodology: A quantitative descriptive research approach was used, involving proximate analysis to measure (Soxhlet method), protein (spectrophotometric method), water (thermogravimetric method), ash (dryashing method), and carbohydrates (proximate method) of rattan shoots. Data were collected from Sibado Village and analyzed in the Chemistry Laboratory of Tadulako University, Palu. An e-pocket book was developed as a learning resource. Main Findings: The results of the study obtained an average fat content of 0.332%, protein content of 2.110% and carbohydrate content of 6.082%. The results of the study were integrated as a learning resource in the form of a local wisdom-based pocket book that had been validated by content experts, design experts, media experts and students with an average value of 81.7%, meaning it is very suitable for use as a learning resource. Novelty/Originality of this study: This study is the first to combine nutritional analysis of Daemonorops robusta with the development of a local wisdom-based educational tool, bridging scientific data and pedagogy to enhance biodiversity awareness, cultural relevance, and contextualized learning in formal education.